P060 A2B adenosine receptor deficiency ameliorates chronic murine Crohn's-like-ileitis. (27th May 2021) - O Connell, L; Olli, K; Wilkinson, C; Collins, C; Jedlicka, P; Aherne, C
Abstract: Background: The A2B adenosine receptor (Adora2b) has been demonstrated to play an immunomodulatory and epithelial barrier protective role in acute murine colitis. A2B agonist treatment during acute murine colitis has been demonstrated to decrease colonic inflammation and damage suggesting targeting the A2B adenosine receptor may protect the intestinal barrier in acute intestinal inflammation. Crohn's disease (CD) is associated with chronic inflammation and damage in the small intestine, most often the ileum. To date the role, if any, of the A2B adenosine receptor in the small intestine and in CD is unknown. Methods: The TNFΔARE model of Crohn's-like ileitis was used to investigate a possible role for A2B in small intestinal inflammation. TNFΔARE mice develop discontinuous, transmural inflammation in the distal ileum that progresses with age and is representative of the chronic inflammation observed in CD. Whole body A2B receptor deficient ( Adora2b -/- ) mice were crossed on to the TNFΔARE background to generate TNFΔARE mice deficient in the A2B adenosine receptor ( Adora2b -/- /TNFΔARE +/- ). Whole ileum was harvested from Adora2b -/- /TNFΔARE +/- and wildtype TNFΔARE mice for histological analysis during early (6–8 weeks), active (10–12 weeks) and chronic disease (>20 weeks). Histological scoring was performed by a board-certified pathologist blinded to the study. Whole tissue was also harvested for digestion to perform live cell counts and cytokine analysis. Results: Histological analysis revealed no significant difference between wildtype and Adora2b deficient TNFΔARE mice during early or active disease. However, during chronic disease Adora2b -/- /TNFΔARE +/- histological scores for active inflammation, chronic inflammation and degree of tissue damage were significantly reduced (approximately 25%) compared to wildtype TNFΔARE mice. This dramatic improvement in histological tissue health in mice with chronic disease was accompanied by an approximately 50% reduction in live cell counts in the ileum of Adora2b -/- /TNFΔARE +/- mice compared to wildtype TNFΔARE mice with a corresponding reduction in pro-inflammatory mediators CXCL1 and IL-1β Conclusion: Our findings demonstrate that sustained loss of A2B receptor expression improves the outcome of chronic small intestinal inflammation. Previous studies demonstrate that A2B receptor expression promotes pro-fibrotic responses in chronic lung fibrosis. Our future studies will address the possible functional role of A2B in pro-fibrotic responses associated with chronic intestinal inflammation.